Large-scale organoid study suggests effects of trisomy 21 on early fetal neurodevelopment are more subtle than variability between isogenic lines and experiments - Czerminski, Jan T.; King, Oliver D.; Lawrence, Jeanne B. (Frontiers in Neuroscience, 2023)
This study examines cortical organoids generated from a panel of isogenic trisomic and disomic iPSC lines (subclones) as a model of early fetal brain development in Down syndrome (DS). An initial experiment comparing organoids from one trisomic and one disomic line showed many genome-wide transcriptomic differences and modest differences in cell-type proportions, suggesting there may be a neurodevelopmental phenotype that is due to trisomy of chr21. To better control for multiple sources of variation, we undertook a highly robust study of ∼1,200 organoids using an expanded panel of six all-isogenic lines, three disomic, and three trisomic. The power of this experimental design was indicated by strong detection of the ∼1.5-fold difference in chr21 genes. However, the numerous expression differences in non-chr21 genes seen in the smaller experiment fell away, and the differences in cell-type representation between lines did not correlate with trisomy 21. Results suggest that the initial smaller experiment picked up differences between small organoid samples and individual isogenic lines, which “averaged out” in the larger panel of isogenic lines. Our results indicate that even when organoid and batch variability are better controlled for, variation between isogenic cell lines (even subclones) may obscure, or be conflated with, subtle neurodevelopmental phenotypes that may be present in ∼2nd trimester DS brain development. Interestingly, despite this variability between organoid batches and lines, and the “fetal stage” of these organoids, an increase in secreted Aβ40 peptide levels—an Alzheimer-related cellular phenotype—was more strongly associated with trisomy 21 status than were neurodevelopmental shifts in cell-type composition.